Priority directions of family social protection system optimization in Ukraine (Journal of actual problems of jurisprudence, 2019)
There is proved the expediency of making changes to the current system of social protection of families in Ukraine. Thereare de fi ned systematic deformations of existing in Ukraine system of social maintenance of families. Proposed priority directions of itsoptimization: reforming of social legislation in the interests of families, the organization of provision of social services, appointmentof social and compensatory payments, regulation of the implementation of social work and the provision of social services; adoptionof state social programs; approval of state social standards, guarantees and regulations; the introduction of various measures of socialprotection.